Electric energy and the environment. Analysis of the emission of air pollutants in the Argentina public utilities - Carnevali, Daniel; Suárez, Carlos E. (Instituto de Economía Energética; Argentina, 1990)
Fil: Carnevali, Daniel. Instituto de Economía Energética, provincia de Río Negro; Argentina